2014
DOI: 10.4236/aad.2014.31002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mild Cognitive Impairment in Individuals Aged over 65 in a Rural Area in North Greece

Abstract: There are no data available on the prevalence of Mild Cognitive Impairment (MCI) in Greece, and the existing information about dementia shows important variations depending on the geographical setting as well as the methodology employed. The aim of this study was to determine the prevalence of MCI in individuals aged over 65 in a rural area in the north part of Greece. From 1428 residents, 678 were finally examined, with a mean age of 73.35 years. Assessments, including neuropsychological testing, neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
2
6
1
3
Order By: Relevance
“…In a study at a rural area of Northern Greece, called M. Alexandros, the prevalence of MCI according to the age groups was 1.6% for the 65- to 69-year age group, 1.7% for the 70- to 74-year age group, 4.3% for the 75- to 79-year age group, and 2.7% for those aged 80+ group. 30 In the same study, the prevalence of MCI due to depression was 8.8%, a percentage similar to ours (8.6%), and 5.9% had only depression, a percentage much lower than ours (33.9%). A previous study in the municipality of Pylaia, an urban area in Thessaloniki, had indicated higher numbers of prevalence of dementia: 4.24% for the 70- to 74-year age group, 10.7% for the 75- to 79-year age group, 10.64% for the 80- to 84-year age group, 11.8% for the 85- to 89-year age group, and 36.7% for those aged 90+ group (Figure 3).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In a study at a rural area of Northern Greece, called M. Alexandros, the prevalence of MCI according to the age groups was 1.6% for the 65- to 69-year age group, 1.7% for the 70- to 74-year age group, 4.3% for the 75- to 79-year age group, and 2.7% for those aged 80+ group. 30 In the same study, the prevalence of MCI due to depression was 8.8%, a percentage similar to ours (8.6%), and 5.9% had only depression, a percentage much lower than ours (33.9%). A previous study in the municipality of Pylaia, an urban area in Thessaloniki, had indicated higher numbers of prevalence of dementia: 4.24% for the 70- to 74-year age group, 10.7% for the 75- to 79-year age group, 10.64% for the 80- to 84-year age group, 11.8% for the 85- to 89-year age group, and 36.7% for those aged 90+ group (Figure 3).…”
Section: Discussionsupporting
confidence: 67%
“…The studies on the prevalence of dementia and MCI in Southern Europe, 26 28 and Greece, in particular, are sparse. 29 31 However, the prevalence of depression or its relation with cognitive decline has examined extensively in Greek area. 31 36 The aim of this study is to examine the prevalence of cognitive impairment and depression symptoms in a rural Greek population, residing on the island of Crete, the birthplace of Mediterranean diet.…”
Section: Introductionmentioning
confidence: 99%
“…According to an Italian study, the mean age of people with dementia in Alzheimer's disease (neurodegenerative dementia) is lower (73.02 ± 7.40 years) than in the current study (81.72 ± 7.73 years) [9]. According to a research conducted in the northern part of Greece among village inhabitants at the age of 65 or older, the diagnosis rate of dementia was significantly lower (2.4%) than in the current study (94.3%), even when compared to young adults up to 65 years of age (5.7%) [10]. The early development of dementia in Alzheimer's disease beginning under the age of 65 is related to gene mutations in subsequent generations (sibling, parent, grandparent with Alzheimer's disease) [11].…”
Section: Discussioncontrasting
confidence: 75%
“…Another limitation is that more females than males participated in the present study. However, it is widely known that AD affects more female than male participants, which is indicative of the prevalence of AD [105][106][107], while other similar approaches have found no differences with respect to resting state activity between the gender groups [134,135]. Finally, another limitation of the current study is the lack of follow-ups in order to investigate the future progression and network changes of SCD.…”
Section: Limitationsmentioning
confidence: 71%
“…Moreover, the independent sample t-test was used for the years of education variable, yielding no statistical difference among the groups, with p = 0.253, while no gender differences were found with respect to gender after chi-squared analysis (p = 0.522). Despite that, in each group of participants, the female participants were more in total compared to male participants, a finding indicative of the prevalence of AD [105][106][107]. However, with respect to age, although we included participants over 60 years old, a statistically significant difference was found in the AD group compared to HC (p = 0.01).…”
Section: Discussionmentioning
confidence: 92%